Regional Historiographical Tradition in Nepal - Subedi, Raja Ram (HISAN: Journal of History Association of Nepal, 2025)
This article explores the evolution of historical writing in Nepal and critically challenges the influence of Western-centered perspectives on its historiography. It explains that in earlier times, Nepal’s history was mainly preserved through religious texts and genealogical Sanskrit traditions, which are often undervalued or labeled as mythical by modern scholars despite their historical significance. The paper points out those Western-influenced academic practices have largely sidelined these indigenous sources and limited their inclusion in formal studies. It also reviews the early documentation of Nepal’s history by foreign scholars such as Bhagwanlal Indraji, William Kirkpatrick, and Francis Buchanan Hamilton, whose interpretations were often shaped by colonial viewpoints and tended to depict Nepal as dependent on external powers like the Gupta Empire, British India, or Tibet. By examining these external accounts alongside traditional sources, the article stresses the importance of adopting a more balanced and critical perspective. It ultimately argues that a proper understanding of Nepal’s past requires the recognition and systematic study of its indigenous historical traditions.